2007
DOI: 10.1007/s10549-007-9632-6
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of basal-like breast cancer

Abstract: Risk factors for the newly identified "intrinsic" breast cancer subtypes (luminal A, luminal B, basal-like and human epidermal growth factor receptor 2-positive/estrogen receptor-negative) were determined in the Carolina Breast Cancer Study, a population-based, case-control study of African-American and white women. Immunohistochemical markers were used to subtype 1,424 cases of invasive and in situ breast cancer, and case subtypes were compared to 2,022 controls. Luminal A, the most common subtype, exhibited … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

53
602
12
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 733 publications
(682 citation statements)
references
References 85 publications
53
602
12
3
Order By: Relevance
“…Results from our cohort also showed that the basal phenotype/p53 positive TNBC is more common in African Americans compared to Caucasians. Our results are consistent with the Carolina Breast Cancer study and others [4,15,17,18]. Awareness of these associations between intrinsic biologic differences and different tumor phenotypes, as well as the prevalence of different tumor phenotypes in different ethnic groups is becoming more important for successful application of individualized targeted therapies.…”
Section: Discussionsupporting
confidence: 91%
“…Results from our cohort also showed that the basal phenotype/p53 positive TNBC is more common in African Americans compared to Caucasians. Our results are consistent with the Carolina Breast Cancer study and others [4,15,17,18]. Awareness of these associations between intrinsic biologic differences and different tumor phenotypes, as well as the prevalence of different tumor phenotypes in different ethnic groups is becoming more important for successful application of individualized targeted therapies.…”
Section: Discussionsupporting
confidence: 91%
“…Therefore, at least two types of HER2 gene-amplified breast carcinomas exist (ER-positive and ER-negative). Because several risk factors for developing basal-like breast cancer have been identified (e.g., BRCA1 mutations carriers and young African-American women), and there are no known specific risk factors (including no apparent interaction with race or age) for the HER2-enriched subtype, 1,21,22 it appears reasonable to etiologically consider basal-like and HER2-enriched breast carcinomas as two different breast cancer diseases. 23 Moreover, the basal-like breast cancer subtype displays an obvious and strong common biology, whereas the HER2-enriched subtype solely describes the occurrence of a high but imperfect correlation with HER2 gene-amplification status.…”
mentioning
confidence: 99%
“…estrógeno (RE), receptores de progesterona (RP), HER 2, Ki67, citoqueratinas de alto peso molecular 5 y 6 (CK5/6), citoqueratinas de bajo peso molecular 8 y 18 (CK 8/18), y receptor para el factor de crecimiento epidérmico (EGFR), es posible catalogar los carcinomas de mama en subtipos equivalentes a los determinados por expresión génica (7,8,9) . El objetivo del presente estudio es clasificar los carcinomas de mama en subtipos moleculares mediante la aplicación de marcadores de inmunohistoquímica, así como determinar las características clínicas, patológicas, y pronósticas de sobrevida global en los diferentes fenotipos moleculares.…”
Section: Mensajes Claveunclassified